Integration of Managerial Roles, Motivation, and Supervision of Madrasah Heads in Improving Student Achievement - Huda, Miftahul; Wafa, Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to analyze the role of madrasah heads in improving student learning achievement at Madrasah Aliyah Nahdlatul Muslimin Undaan Kudus by using a qualitative approach through case study methods. Data was collected through in-depth interviews with madrasah heads, deputy heads of curriculum and student affairs, participatory observation, and documentation of student achievements. Data analysis was carried out using the Miles and Huberman model which included data reduction, data presentation, and drawing conclusions by triangulating sources. The results of the study show that the head of the madrasah carries out three main roles. First, as a manager, the head of the madrasah effectively plans, organizes, and supervises academic and non-academic programs through a collaborative approach. Second, as a motivator, the head of the madrasah provides psychological encouragement and appreciation to teachers and students, thereby increasing the spirit of learning and achievement. Third, as a supervisor, the head of the madrasah supervises learning on lesson plans, annual programs, and semester programs, as well as encourages teacher professional development through training and workshops. This study confirms that the leadership of madrasah heads that integrates managerial, motivational, and supervisory functions makes a significant contribution to improving students' academic and non-academic achievements. This study also recommends strengthening the capacity of madrasah heads as agents of change in educational transformation through participatory and collaborative leadership models.